Determination of load-carrying capacity of back-to-back C-profile beams subjected to pure bending - Czechowski, Leszek; Kotełko, Maria; Jankowski, Jacek; Ungureanu, Viorel; Sanduly, Annabella; Kaźmierczyk, Filip (Archives of Civil Engineering, 2026)
The present work concerns the strength analysis of back-to-back steel C-profiles subjected to pure (4-point) bending. The load-carrying capacities of considered beams were determined using experimental and numerical tests. Numerical analysis was performed using the finite element method (Ansys code) considering the full nonlinearity of the material and large displacement and strains. Three different numerical models were elaborated to adjust the results to experimental ones. The one of numerical models was based on assumption of doubled wall thickness. The experiments have been conducted for beams with two different thicknesses. In the study, the length of the beam and the distance between the supports were taken into account. Two C-beams designated for the tests were connected using spots welds deployed at adequate places. The results of numerical simulations based on different approaches have been compared with those of experimental ones. In general, the results of the numerical simulations are in a good agreement with the experiment.